The Enhancement of Professional Teaching Capacity for Social Studies Teachers - Tanthikun, Kheminthar; Sakbeerakul, Thongsai (Academic Journal of MBU Lanna, 2023)
The objectives of this research were: 1) to study the need for teaching competency development 2) to improve teaching competency 3) to reflect the results of teaching competency development 4) to measure student satisfaction with the development of teaching competency. The sample group included a total of 16 students/persons from the Teaching Social Studies Department in the academic year 2020, obtained through purposive sampling. The research was conducted in four steps: 1) studying the competency requirements used in teaching management, 2) developing and applying a teaching competency model, 3) actual application to the target group, and 4) Activity Reflection Report (AAR). The results of this research found that: the study of the needs of professional teaching students was at the highest level, particularly in terms of strategies to motivate learners. Regarding the planning aspect, the setting of the learning atmosphere and classroom management represented the second level of need. The reflection of learning management resulted in the lowest level of need. The feedback and evaluation from students indicated that the overall teaching aspect of the students was at a high level. The results reflected the outcomes of competency development, with 90 percent of students and teachers participating in the practice, providing qualitative feedback. Students had practical and actual results in a total of 11 activities, all aimed at promoting diverse learning in social studies, religion, and culture. Media production for learning activities was also included. Overall, student satisfaction with the development of teaching among professional students in the field of teaching social studies was at a high level.